Singing Sam - Bulla, Clyde Robert; Paradise, Susan (New York : Random House, 1989)
Tired of caring for his new dog, a spoiled boy gives him to a young girl who discovers that the dog can sing.
240
Keywords: Dogs -- Fiction; Behavior -- Fiction